Redesigning the AIDS response for long-term impact - Heidi J Larson; Stefano Bertozzi; Peter Piot (The World Health Organization, 2011)
Three decades since the human immunodeficiency virus (HIV) was identified, the pandemic of acquired immunodeficiency syndrome (AIDS) has developed into diverse epidemics around the world. In many populations, HIV infection has become endemic. While there is good progress on expanding access to treatment, with an estimated 6.6 million people on antiretroviral therapy at the end of 2010, prevention efforts are still highly inadequate with 2.6 million new infections occurring in 2009. Demand for treatment is increasing while funding is becoming more scarce and activism is waning. In 2007, the Joint United Nations Programme on HIV/AIDS (UNAIDS) established an independent forum called aids2031 to take a critical look at the global HIV/AIDS response. This paper outlines four key areas for a redesigned AIDS response based on the deliberations of this initiative and on the learning and experience of the first three decades of the epidemic: (i) a new culture of knowledge generation and utilization; (ii) transformed prevention and treatment to increase effectiveness; (iii) increased efficiency through better management and maximizing synergies with other programmes; and (iv) investment for the long term. Across all these areas is a strong emphasis on local capacity building, leadership, programme priorities and budgets.